2017
DOI: 10.3892/ol.2017.6695
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126 inhibits cell viability and invasion in a diabetic retinopathy model via targeting IRS-1

Abstract: Abstract. Diabetic retinopathy (DR) is a sight-threatening complication of diabetes. IRS-1 was predicted to be the target gene of microRNA-126 (miR-126). The present study was designed to illustrate the involvement of miR-126 in the regulation of DR via targeting IRS-1. The present study revealed that the expression of miR-126 was significantly decreased while IRS-1 expression was increased in endothelial cells (ECs) and retinal pericytes (RPs) from a DR mouse model compared with healthy controls. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Finally, as an insulin feedback was reported to limit the efficacy of PI3K inhibition in several tumor models (Hopkins et al ., ), we checked for the effects of the combined PIK‐75 plus vemurafenib therapy on the expression of the IRS‐1. IRS‐1, a key molecule in signal transduction between the insulin receptor and PI3K, was demonstrated to be a target gene of miR‐126 in different cancers (Fang et al ., ). Expression studies, besides confirming IRS‐1 down‐regulation in miR‐126‐transduced A375M melanoma compared with TripZ control cells, showed the strong induction of IRS‐1 in PIK‐75 + vemurafenib cotreated A375M cells, a result suggestive of the association of its activation with drug resistance.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, as an insulin feedback was reported to limit the efficacy of PI3K inhibition in several tumor models (Hopkins et al ., ), we checked for the effects of the combined PIK‐75 plus vemurafenib therapy on the expression of the IRS‐1. IRS‐1, a key molecule in signal transduction between the insulin receptor and PI3K, was demonstrated to be a target gene of miR‐126 in different cancers (Fang et al ., ). Expression studies, besides confirming IRS‐1 down‐regulation in miR‐126‐transduced A375M melanoma compared with TripZ control cells, showed the strong induction of IRS‐1 in PIK‐75 + vemurafenib cotreated A375M cells, a result suggestive of the association of its activation with drug resistance.…”
Section: Resultsmentioning
confidence: 97%
“…In tumor samples, we showed reduced proliferation and increased apoptosis as indicated by Ki67 and caspase 3 modulations. According to recently published data (Hopkins et al ., ), miR‐126 also appeared able to disrupt the insulin regulatory loop by reducing the expression of the key factor IRS‐1, reported as a target gene of miR‐126 (Fang et al ., ). In addition, proteomic analysis showed the effectiveness of miR‐126 action on the mTOR pathway, one of the key controllers of cancer metabolism (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, in the same individuals, only a few circulating miRNAs were detected in vitreous compared with serum [10]. In ▶ table 1, we have summarized miR-126 [11,12], miR-211 [13], miR-93 [14][15][16], miR-122 [17], miR-221 [18], miR-27b and miR-320a [8], miR-150-5p, miR-21-3p and miR-30b-5p [19] as biomarkers in DR over the past 5 years. At the same time, we have focused on miRNAs in vitreous humor (VH) of DR, such as miR-126 [20], miR-19a and 27a [21], miR-29a [22,23], miR-93 and 20a [21], and miR-200b [24] in ▶ table 2.…”
Section: Circulating Mirnas As Biomakers In Drmentioning
confidence: 99%
“…Moreover, it has been demonstrated that insulin receptor substrate 1 (IRS-1) is a target gene of miR-126 in endothelial cells and retinal pericytes in an animal model of DR. Furthermore, the interaction between them downregulates the expression of PI3K/Akt pathway proteins and negatively influences the viability and invasion of endothelial cells and retinal pericytes isolated from a mice model of DR [150]. The PI3K/Akt pathway is crucial for a long-term upregulation of VEGF, which is an angiogenic factor involved in the pathogenesis of DR.…”
Section: Mirna In Dr: Role In Oxidative Stress and Inflammatory Signamentioning
confidence: 99%